Ampliación de la Unión Europea, polarización social y pobreza en “las historias de éxito”. The expansion of the European Union, social polarization and poverty in the “success stories”. - Luengo, Fernando (Papeles del Este, 2006)
This article analyses the social balance of the former communist countries with the highest income levels, now the newest members of the European Union, during the period between 1995 and 2003-2004. During these years, inequalities increased in spite of economic growth. Poverty affects in particular children, the long-term unemployed, and regions of the countries that are far from the economic growth centres. The causes for these developments are found in weak growth employment elasticity, in an increase in the salary differences and in social spending very much below the European community average. What occurred in these countries demonstrates that growth does not make up for the social costs associated with the introduction of the market economy.